Zmiany w spoczynkowej równowadze miedzy poziomem kortyzolu i testosteronu we krwi sportowców w odpowiedzi na pierwsze treningi po okresie roztrenowania - Obminski, Z.; Tkaczyk, J. (Sport wyczynowy, 2002)
Resting levels of cortisol (C) and testosterone (T) in blood were determined senior male (n = 8) and female (n = 8) judoists throughout 4 consecutive days of the first training microcycle following a detraining period. Mean cortisol concentrations showed sex- and time-related differences. Mean concentrations were highest on the first training day (560 ± 93 and 797 ± 210 nmol/L in men and women, respectively) decreasing afterwards and reaching lowest value on Day 3 (433 ± 86 and 524 ± 147 nmol/L in men and women, respectively). Mean cortisol concentration over the entire microcycle was significantly lower in men than in women (489 ± 97 and 634 ± 196, respectively). Mean testosterone concentrations in men were relatively stable and ranged from 16.5 ± 2.0 to 18.8 ± 2.8 nmol/L. In women, the day-to-day changes differed significantly, the concentrations decreasing from 2.4 ± 0.6 to 1.3 ± 0.4 nmol/L. After 3 days of training, the anabolic/catabolic index (T/C) slightly increased in men and decreased in women.